INFLUENCE OF FINANCIAL KNOWLEDGE AND RELIGIOSITY TOWARDS FINANCIAL MANAGEMENT BEHAVIOR WITH FINANCIAL ATTITUDE AS A MODERATION VARIABLE - Fadia Zen; Achmad Murdiono; Lulu Nurul Istanti (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
Indonesia is one of the countries with a primarily small and medium-sized enterprise (SME) based economy. Cooperatives are a vital component of Indonesia's economic landscape, and their development is not limited to conventional cooperatives initiated by the community. It also extends to cooperative groups associated with Islamic boarding schools. These boarding schools serve not only as religious and social education institutions but also as agents of societal development and social change. Despite their potential for economic empowerment, the progress of cooperative boarding schools tends to be slower compared to conventional cooperatives. This research aims to examine the influence of financial knowledge and religiosity on financial management behavior, with financial attitude as a moderating variable. The study employs a quantitative approach and targets Kopontren administrators in the Regency of Blitar, using Confirmatory Factor Analysis (CFA) tests and the Structural Equation Modeling (SEM) method. The research findings indicate that financial attitude and religiosity have an impact, with financial attitude serving as a moderator in the relationship between financial knowledge and financial management behavior. However, religiosity does not have a significant influence on financial management behavior. The results of this research are expected to provide a foundation for developing a model of financial management behavior for Kopontren administrators and government initiatives aimed at empowering Kopontren institutions.